Diversity of Species and Structure of Macrozoobentos Communities in the Waters of Bagik Batu Beach, Lombok Island, West Nusa Tenggara - Irwansah; Ermila Mahariyanti (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Macrozoobentos are a key biological component of coastal ecosystems that act as indicators of habitat quality and are important nodes in the aquatic nutrient cycle. Bagik Batu Beach in Jerowaru District, East Lombok Regency, West Nusa Tenggara is a coastal area that experiences layered ecological pressure due to tourism activities, traditional fisheries, and the conversion of mangrove ecosystems. This study aimed to analyze the type diversity, uniformity, dominance, abundance, frequency of attendance, and structure patterns of benthic macrofauna communities at three observation stations. Sampling was done using the line transect method combined with a square measuring 1×1 m². At each station, 2 transects are made along 50 m perpendicular to the coastline, with square placement every 10 m so that 5 square plots per transect are obtained, a total of 30 plots per station. The results of the study found 15 species (Anadara sp., followed by Cerithium sp., Trachycardium sp., Tapes literatus, Mactra grandis, Circe scripta, Pitar citrinus, Canarium Sp., Pinna bicolor, Holothuria edulis, Venus sp., Modiolus metcalfei, Protoreaster sp. and Synapta maculata from 4 taxonomic classes (Bivalvia, Gastropoda, Holothuridea, and Asteroidea) with a total of 589 individuals. The Shannon-Wiener index (H') is around 2.41 categorized as medium diversity, the Pielou uniformity index (E) is around 0.89 is categorized as evenly categorized and the Simpson dominance index (C) is around 0.11 categorized as low dominance. Anadara sp. is the species with the highest abundance in the entire station. The conditions of the physico-chemical parameters of the waters are still in the optimal range for macrozoobenthose life.